Risk prediction after TIA: the ABCD system and other methods. - Giles, M; Rothwell, P (2008)
Transient ischemic attack (TIA) is common in the elderly and total numbers are likely to increase with the aging of the population. The risk of stroke early after TIA has recently been shown to be approximately 5 percent at 7 days and 10 to 15 percent at 3 months, while overall cardiovascular risk is increased in the longer term. The ABCD system (Age, Blood pressure, Clinical features, Duration of symptoms) is a clinical score that can be rapidly worked out at the time of presentation and reliably predicts early risk of stroke. It can be used in patient triage to secondary care, informing public education and in the effective targeting of secondary prevention. The vascular territory and etiology of the TIA and results of cerebral imaging can also be used to predict early risk of stroke but the degree of the interaction between all these factors is uncertain.